The perception and experience of dignity in the care of older adults in nursing homes: A Meta-aggregation protocol - Chunxiang Li; ZhengKe Li; Jiayi Xu; Rongyu Hua (PLoS ONE, 2026)
Background The concept of dignity in the context of nursing home care for older adults remains vague, hindering further research in this area. Aim This systematic review aims to conceptualize the characteristics of dignity in nursing home care for older adults, with attention to Chinese cultural perspectives. Methods The six international databases SCOPUS, PubMed, CINAHL, Embase, Ovid, and PsycInfo, and one Chinese database CNKI will be searched from inception to 31st August 2025, and eligible studies will be primarily evaluated. The literature selected will focus on primary studies that explore older adults’ perceptions of dignity who have resided in the nursing home for at least one month, encompassing their experiences and the factors influencing dignity. This review will draw exclusively on peer-reviewed journal articles, with no language restrictions applied. Grey literature — including dissertations, theses, conference proceedings, and institutional reports — will not be considered for inclusion. The systematic review will adhere to the PRISMA 2020 guidelines and will be registered with PROSPERO. Three reviewers (a lead researcher, a graduate student assistant, and a non-nursing assistant) will primarily screen the titles and abstracts separately. And two professional reviewers (the lead researcher and the graduate student assistant) continue to select studies and extract data independently following the predesigned data extraction forms. Any discrepancies will be documented and resolved by a third external reviewer until consensus is reached. The quality of the included literature will be assessed using the Joanna Briggs Institute (JBI) critical appraisal tools, and the findings will be synthesized using the meta-aggregation approach. Expected outcomes This review is expected to identify key themes across two domains: inherent dignity (satisfying physical needs) and social dignity (individuality, identity and independence). It will also identify the key factors influencing dignity, including personal factors (functional status), organizational factors (staff attitudes, organizational ethical environment), and sociocultural factors (Chinese cultural norms such as collectivism). The results of the dignity in care will help healthcare providers implement dignified care in nursing homes.